The WTO Reference Paper meets EU common regulatory policy in CETA - Hildegunn Kyvik Nordås (Örebro University School of Business, 2020)
International trade and investment in telecommunications are governed by the World Trade Organization's (WTO) General Agreement on Trade in Services (GATS) and its Annex and Reference Paper (RP) on telecommunications. This paper discusses whether the 25-year old WTO framework is still fit for purpose. It makes two contributions to the literature. First, it offers a systematic comparison between the provisions in the RP, the EU-Canada Comprehensive Economic and Trade Agreement (CETA) and EU common regulatory framework. GATS builds on an outdated classification of telecommunications which is repeated in the CETA. The RP obliges countries to regulate interconnection, which is also largely repeated in CETA, although regulatory forbearance is permitted. CETA does not offer new market access in telecommunications to either party. Second, the paper investigates empirically whether binding regulation in trade agreements strengthen market openness, measured by imports of telecommunications services, and finds that it does not. The paper concludes that trade agreements may not be suitable for international cooperation on telecommunications regulation. Trade agreements run the risk of making regulation hostage to unrelated trade policy issues while adopting the RP runs a risk of legal obligations to over-regulate telecommunications.
Keywords: F13; F14; L86; 330; Telecommunications; International trade; WTO reference paper; EU; CETA